Development of fortified cookies from dehydrated swamp taro (Cyrtosperma merkusii) - Pahila, Jade Go (2011.)
A fortified cookie from the dehydrated swamp taro combined with all-purpose wheat flour was developed.
Sotech thesis.
Keywords: Swamp taro; Cyrtosperma merkusii